Shaping knowledge complex socio-spatial modelling for adaptive organizations - O'Brien, Jamie (Oxford, UK Chandos Pub., 2014)
This text provides a guide to the multi-disciplinary theme of how knowledge may be reconfigured so as to enhance experience, enable participation and augment environments. It includes an introduction to the key tools for thinking required by decision-making professionals in today's knowledge-intensive landscapes, and equips them with key skills to capitalize on knowledge resources, offering practical methods and insights for modelling knowledge-driven domains.
1. Introduction and case study -- 2. Innovation, agency and technology -- 3. The dynamics of innovation -- 4. Modelling knowledge dynamics -- 5. Modelling socio-spatial agents -- 6. Case studies in socio-spatial change -- 7. Reasoning with graphs -- 8. Decisions and arguments -- 9. Directions for adaptive planning.
Includes bibliographical references and index.
Keywords: Knowledge management; Knowledge representation (Information theory)